Pedagogical Guide to the Improvement of Family Environment and School Performance in Sixth Year. - Carabali, Luis Antonio; Cabrera Cabrera, Diana; Piñera Concepción, Yadyra de la Caridad; Sánchez Andrade, Ph.D. Virginia (Revista Minerva, 2025)
The objective of this research was to design a pedagogical guide for the improvement of the link between the family environment and school performance in the sixth year of the "“9 de Octubre”" School. A quantitative and descriptive approach methodology was used, through surveys of parents and teachers, observation sheets and documentary review. The results showed that 62% of the families have low involvement in their children’s education, limiting the academic and emotional support necessary for their school performance; 25% show moderate participation and only 13% demonstrate high commitment. In addition, teachers pointed out that most students lack support in homework and educational resources, while the observations reflected difficulties in study habits and participation in the classroom. It is concluded that the lack of intra-family communication and poor academic support affect learning, so a series of strategies such as family incentives, training workshops and recognition systems were proposed to strengthen the relationship between the school and families. The proposal, validated through participatory methodologies, seeks to generate a positive impact on the academic and social development of students.